2004
DOI: 10.1074/jbc.m401864200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Rod Photoreceptor cGMP Phosphodiesterase α-Subunit Gene Promoter

Abstract: To understand the factors controlling expression of the cGMP phosphodiesterase type 6 (PDE6) genes, we have characterized the promoter of the human PDE6A gene that encodes the catalytic ␣-subunit. In vivo DNase I hypersensitivity assays revealed two sites immediately upstream of the PDE6A core promoter region. Transient transfection assay in Y79 cells of constructs containing varying lengths of the promoter region showed a decrease in promoter activity with increasing length. The most active segment contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…It was reported that Crx, Nrl, and Nr2e3 synergistically regulate the expression of rod-specific genes (31,(38)(39)(40)(41)(42). In the current study, we found that although the expression levels of Crx, Nrl, and Nr2e3 were similar between control and Rax iCKO (P4 ¡ P20) mouse retinas, the levels of transcripts of rod-specific genes significantly decreased in the Rax iCKO (P4 ¡ P20) mouse retina (Fig.…”
Section: Resultsmentioning
confidence: 40%
“…It was reported that Crx, Nrl, and Nr2e3 synergistically regulate the expression of rod-specific genes (31,(38)(39)(40)(41)(42). In the current study, we found that although the expression levels of Crx, Nrl, and Nr2e3 were similar between control and Rax iCKO (P4 ¡ P20) mouse retinas, the levels of transcripts of rod-specific genes significantly decreased in the Rax iCKO (P4 ¡ P20) mouse retina (Fig.…”
Section: Resultsmentioning
confidence: 40%
“…Another key transcription factor, Nrl, which regulates many photoreceptor-specific genes and the terminal differentiation of rod photoreceptors (98)(99)(100)(101)(102)(103), is reduced slightly (by ∼1.2 fold) in the retina of miR-183C…”
Section: Discussionmentioning
confidence: 99%
“…NRL is established as a positive transcriptional regulator of rod-specific genes (28,31,33,(45)(46)(47). To examine whether NRL can directly modulate cone-specific promoters, we screened 3 kb of 5Ј upstream promoter regions of the two cone-expressed genes, Thrb [encoding Tr␤2 that is involved in M-cone differentiation, (14)] and S-opsin, for the presence of Nrl or Maf response element (NRE/MARE) (46).…”
Section: Ectopic Expression Of Nrl Can Suppress Cone Function and Indmentioning
confidence: 99%